Androgen insensitivity syndrome - Güleç-Ceylan, Gülay; Özbey, Ülkü; Yüce, Hüseyin (My University, 2007)
The cases with androgen insensitivity syndrome are males as genetic sex and they have testises. But, their external genitalia is not normally male. This syndrome is inherited X-linked recessive and its incidence is 2-5/100000. Conventional cytogenetic analysis was performed for the case who was 4 years old, had no family history and applied for the inguinal hernia. At the case who seemed phenotypically female, pelvic ultrasonography showed hypoplastic uterus and 24x10 mm mass localized at inguinal channel that was adjusted as testls. Immatur testis tissue was determined at the pathologic analysis from the biopsy of this cystic mass. Hormone analysis performed normal degrees except from the low level of luteinizing hormone (LH). At the end of the conventional cytogenetic analysis, the karyotype of the case was determined as 46, XY. The case was analysed by also interphase fluorescence in situ hybridization (FISH) technique as well as a number of metaphase analysis to eliminate the mosaicism. In the presentation of this rarely seen case, the courses that will be followed at appropiate sociopsychological approaches by genetic counselling, clinical follow-up and diagnosis progression are discussed based on the literature.
Androjen duyarsizli?i sendromu
Keywords: luteinizing hormone; androgen insensitivity syndrome; case report; chromosome analysis; hormone determination; human; karyotype 46,XY; luteinizing hormone blood level; male; preschool child; review